Evaluation of the enhanced recovery after surgery protocol in living liver donors. Issue 8 (24th July 2018) - Khalil, Ahmed; Ganesh, Swaytha; Hughes, Christopher; Tevar, Amit D.; Hasche, John J.; Esper, Stephen; Humar, Abhinav
Abstract: Background: Enhanced recovery after surgery (ERAS) protocol has proven to be effective in many surgery fields in controlling pain and promoting early recovery. Application of the (ERAS) protocol in living donor liver patients is a new step to promote early recovery. Methods: We analyzed outcomes in two groups. Group A included the living donors who had the ERAS protocol applied (n = 30), and Group B included donors who had their surgery before the ERAS protocol (n = 30). All donors had the same incision. The ERAS protocol involved a multimodality methods. This included intravenous ketamine and lidocaine intraoperatively with single dose intrathecal morphine and local injection of long‐acting bupivacaine. The postoperative regimen included intravenous ketamine, lidocaine, ketorolac, and narcotics as PRN. Results: Pain on the first three postoperative days was significantly lower in Group A ( P  < 0.05). Narcotics were also significantly lower in Group A ( P  < 0.01). Return of bowel function occurred earlier by 1 day in Group A ( P  < 0.003). Group A patients could tolerate a regular diet by postoperative day (POD) three vs four in Group B patients ( P  = 0.0057). Mean length of stay was lower in Group A, but not statistically significant. Conclusions: Enhanced recovery after surgery protocol was effective in minimizing postoperative pain and helped to decrease the postoperative narcotics and helped early recovery.